Academics' perspective of the educational leaders' innovative leadership influence in the management of hybrid learning - Muhammad Syukri Abd Hamid (Kulliyyah of Education, International Islamic University Malaysia, 2022)
This study intended to explore thorough discernments of educational leaders on the function of innovative leadership style in vitally contributing to the implementation of hybrid learning at the university level aiming to understand the role of educational leaders in reference to adopting innovative leadership style for the execution of the matter. The recent pandemic had forced drastic change in reshaping the approaches and designs in the setting of formal education which demands the implementation of hybrid learning to be executed comprehensively in order to accommodate the situation. Through a qualitative research design the targeted informants consisted of head of departments selected from various kulliyyahs in International Islamic University Malaysia (IIUM) using purposive sampling technique. The data collection method used was in-depth semi-structured interviews. Data gathered from the interviews were transcribed using thematic analysis and themes were extracted to answer all of the research questions. Findings had shown relevant support for the mentioned leadership style towards the effectiveness of hybrid learning, and had highlighted the challenges faced in abruptly implementing hybrid learning, and interesting suggestions for considerations.